MANAJEMEN KELAS DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN DI SMPN 8 KARAWANG - Paujiah, Popon; Nugroho, Muhammad Adi; Nourmahayati; Hinggil (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2026)
Classroom management is one of the important factors in creating an effective, conducive, and student-centered learning process. Good classroom management not only helps maintain order during the learning process but also influences student engagement, learning motivation, and the achievement of learning objectives. This study aims to analyze the implementation of classroom management, supporting and inhibiting factors, teachers’ strategies in improving learning effectiveness, and the ideal conditions for effective learning at SMPN 8 Karawang. The research location was selected because the school implements various classroom management strategies that actively involve teachers and students in creating a conducive learning environment. This study employed a descriptive qualitative approach involving one principal, five teachers, and fifteen students as research informants. The informants were selected using purposive sampling techniques based on their involvement in the learning and classroom management processes. Data were collected through in-depth interviews, direct classroom observations, and documentation studies. Data validity was ensured through source triangulation and technique triangulation to maintain the accuracy of the research findings The results showed that classroom management at SMPN 8 Karawang was implemented through several main strategies, including establishing classroom agreements collaboratively with students, applying discipline consistently, arranging flexible seating based on learning needs, and using interactive teaching methods and visual-based learning media. These strategies were able to increase student participation in learning, build discipline, and create a more comfortable and conducive learning atmosphere. In addition, teachers applied emotional approaches through positive communication to build better learning relationships with students. Based on the findings, it can be concluded that effective classroom management contributes to improving learning effectiveness by creating an active, orderly, and conducive learning environment. This study provides practical implications for teachers and schools to improve the quality of classroom management through more innovative, interactive, and student-oriented learning strategies